Behavioural economics, consumer behaviour and consumer policy: state of the art - REISCH, LUCIA A.; ZHAO, MIN (Behavioural Public Policy, 2017)
Counter to the traditional assumption of neoclassical economics that individuals are rational Homo oeconomici that always seek to maximize their utility and follow their ‘true’ preferences, research in behavioural economics has demonstrated that people's judgements and decisions are often subject to systematic biases and heuristics, and are strongly dependent on the context of the decision. In this article, we briefly review the transition of research from neoclassical economics to behavioural economics, and discuss how the latter has influenced research in consumer behaviour and consumer policy. In particular, we discuss the impacts of key principles such as status quo bias, the endowment effect, mental accounting and the sunk-cost effect, other heuristics and biases related to availability, salience, the anchoring effect and simplicity rules, as well as the effects of other supposedly irrelevant factors such as music, temperature and physical markers on consumers’ decisions. These principles not only add significantly to research on consumer behaviour – they also offer readily available practical implications for consumer policy to nudge behaviour in beneficial directions in consumption domains including financial decision making, product choice, healthy eating and sustainable consumption.